Optimization of Spectrophotometric and Fluorometric Assays Using Alternative Substrates for the High-Throughput Screening of Lipase Activity - Jun-Young Park; Jisu Ha; Yoonseok Choi; Pahn-Shick Chang; Kyung-Min Park (Journal of Chemistry)
The effects of reaction conditions on the spectrophotometric and fluorometric assays using alternative substrates (p-nitrophenyl palmitate and 4-methylumbelliferyl oleate) were investigated to optimize them for the high-throughput screening of lipase activity from agricultural products. Four model lipases from Chromobacterium viscosum, Pseudomonas fluorescens, Sus scrofa pancreas, and wheat germ (Triticum aestivum) were allowed to hydrolyze the alternative substrates at different substrate concentrations (1–5 mM), operating pH (5.0–8.0), and operating temperatures (25–55°C). The results show that both the spectrophotometric and fluorometric assays worked well at the standard reaction conditions (pH 7.0 and 30°C) for finding a typical lipase, although pH conditions should be considered to detect the catalytic activity of lipases, which are applicable to more acidic or alkaline pH circumstances. To validate the optimized conditions, the high-throughput screening of lipase activity was conducted using 17 domestic agricultural products. A pileus of Pleurotus eryngii showed the highest activity in both the spectrophotometric (633.42 μU/mg) and fluorometric (101.77 μU/mg) assays. The results of this research provide practical information for the high-throughput screening of lipases using alternative substrates on microplates.